Assessment of Knowledge Management System Readiness: A Case Study of IT Consultant Company - Farah Nabilah Muhammad (Jurnal Edik Informatika Penelitian Bidang Komputer Sains dan Pendidikan Informatika, 2023)
In a rapidly changing business environment, companies need knowledge to survive. PT XYZ is a company that stands in the information technology solutions business sector, and consistently focuses its services on customers. Many of the company's projects depend on the best practices and knowledge of employees on previous projects. Company realizes that knowledge plays an important role in PT XYZ. To support the successful implementation of the Knowledge Management System (KMS) in the company, an assessment of the company's level of readiness to be able to implement KMS will be carried out. This study aims to assess the company's Knowledge Management System Readiness using framework based on 15 variable that form the basis of the question for questionnaire. Based on the assessment results, the company's readiness is at level 4. However, two of indicator from Organization Structure factor needs to be improved because it is below the readiness limit which scores 2.8 and 3.2 from the 3.4 limit. This study provides recommendations to improve the company's readiness on the organizational structure factor.